Capital Structure Determinants: Empirical Research on Construction Firms in Malaysia - Maslina, Samiran (2010)
This research is undertaken to identify the capital structure determinants of the construction firms in Malaysia. The research is carried out to ascertain the inter-relationships and the degree of significance between these seven factors which determine the selection of capital structure, i.e. size, profitability, nature of assets (tangibility), non-debt tax shields, liquidity, growth opportunities and tax charge, which incorporates both leverage measures, constituting market leverage ratio level and the book leverage ratio level to relate on which capital structure theory is more applicable to the construction industry players in Malaysia. The outcome of the findings demonstrated that liquidity and growth opportunities are highly negatively significant in determining the capital structure choice of the construction firms in Malaysia, in consistent with the Pecking Order Theory.